Применение предметно-схематических моделей в развитии связной речи детей с ОНР - Королёва, Е.Я. (My University, 2016)
The article reflects the experience in the development of coherent speech of preschool children with EPD with the use of icons, mnemonics, visual material. Introduction of visual models in the educational process allows more focused to develop an impressive speech of children enrich their active vocabulary, consolidate the skills of word formation, describe the items that composes stories.
Keywords: icon; scheme; mnemonics; symbol; model